The effect of prolonged standing at work on the incidence of infertility in male anesthesia technicians - Muhammad Rizki Eko Rahmanto; Azzahra Nabila Putri; Putri Aliya Savira Mootalu; Ayano Kit; Andari Wuri Astuti (Journal of Health Technology Assessment in Midwifery, 2026)
Male infertility accounts for nearly half of infertility cases worldwide and has increasingly been recognized as an occupational health concern, particularly among male anesthesia technicians who are exposed to prolonged standing during surgical procedures, extended working hours, operating room heat, and potential chemical exposure. Prolonged static standing may impair venous circulation and increase scrotal temperature, thereby disrupting spermatogenesis and compromising semen quality. This scoping review aimed to map and synthesize available scientific evidence regarding the association between prolonged standing at work and infertility-related outcomes among male anesthesia technicians and comparable occupational groups. The review was conducted in accordance with the framework proposed by Tricco et al., with systematic literature searches performed in PubMed, Cochrane Library, and Google Scholar for articles published between 2019 and 2025. Original research articles published in English or Indonesian that examined occupational standing duration, static posture, or related physical workload and male reproductive outcomes were included, and study selection followed the Population–Concept–Context (PCC) framework and PRISMA flow diagram. Data extraction and quality appraisal were performed using the Mixed Methods Appraisal Tool (MMAT). Five studies met the inclusion criteria, comprising retrospective cohort, cross-sectional, and longitudinal observational designs, predominantly conducted in China, with one study from Turkey. The findings consistently demonstrated that prolonged standing exceeding 5–6 hours per day was associated with impaired semen quality, including reduced sperm motility and concentration, increased abnormal sperm morphology, and elevated sperm DNA fragmentation index (DFI), with occupational heat exposure and chemical agents acting as additional contributing factors. Oxidative stress was identified as a key biological mechanism underlying sperm dysfunction, and several studies indicated a dose–response relationship between exposure duration and the severity of semen impairment. In conclusion, the available evidence suggests that prolonged standing at work is associated with adverse male reproductive outcomes and may increase the risk of infertility, highlighting male anesthesia technicians as a potentially high-risk occupational group and underscoring the need for ergonomic interventions, occupational risk management, and reproductive health monitoring in healthcare settings.